Effectiveness of Preoperative Psycho-educational Program on Stress of Cardiac Surgery Patients - ali, Sundus; Jacoub, Shirooq (Iraqi National Journal of Nursing Specialties, 2015)
Objective: The study aimed to determine the effectiveness of preoperative psycho - education alprogram on cardiac surgery patients information and their level of stress. And find out the differencesin the Psycho educationalprogram with regard to patients demographic characteristics such as age and gender.Methodology Aquazi-experimental study was carried out to determine the effectiveness ofpreoperative education program on stress for cardiac surgery patients in Baghdad city from the 28th ofMarch, 2010 , to 19th of September ,2011.The preoperative psycho - educational program, as well as the questionnaire was constructed as a tool ofdata collection for the purpose of the study. Purposive (non probability) samples of 40 patients whohave undergone cardiac surgery (CABG &VR) are selected from Ibn AL-Bitar Specialized Center forcardiac surgery. The researcher divided the samples into two equal groups (the study and controlgroups) .Data was analysis through the use of the suitable statistical methods.Results: The results of the study indicates that there are significant differences in the patientsknowledge towards cardiac surgery in the study & control groups through pre-test, post-test.Recommendations: The study recommended that such program should be implemented in the form ofsession for the patients before undergone cardiac surgery to prepare them to cope with the stress andimprove their knowledge.